P307 High frequency of Deep Infiltrating Endometriosis in patients with Inflammatory Bowel Disease: a nested case-control study. (30th January 2023) - Neri, B; Russo, C; Mossa, M; Martire, F G; Aikaterini, S; Mancone, R; Calabrese, E; Rizzo, G; Exacoustos, C; Biancone, L
Abstract: Background: Inflammatory Bowel Disease (IBD) and endometriosis are chronic inflammatory diseases occurring in young women, sharing some clinical manifestations. We aimed to investigate, in a multidisciplinary approach, symptoms, type and site of pelvic endometriosis in IBD patients versus non-IBD Controls with endometriosis. Methods: In a prospective nested, case-control study, all female premenopausal IBD patients showing symptoms compatible with endometriosis were enrolled. Patients were referred to dedicated gynecologists for assessing pelvic endometriosis by transvaginal sonography (TVS). Each IBD patient with endometriosis (Cases) was retrospectively matched for age (±5 years) and body mass index (±1) with 4 patients with endometriosis at TVS, but no-IBD (Controls). Data were expressed as median [range], the Mann-Whitney or Student-t and χ2 tests were used for comparisons. Results: Endometriosis was diagnosed in 25 (71%) out of 35 IBD patients with compatible symptoms including 12 (52.6%) Crohn's Disease and 13 (47.4%) Ulcerative Colitis patients. Dyspareunia and dyschezia were significantly more frequent in Cases vs Controls (25 [73.7%] vs 26 [45.6%]; p=0.03). At TVS, deep infiltrating endometriosis (DIE) and posterior adenomyosis were significantly more frequent in Cases vs Controls (25 [100%] vs 80 [80%]; p=0.03 and (19 [76%] vs 48 [48%]; p=0.02). Conclusion: Endometriosis was detected in two/thirds of IBD patients with compatible symptoms. The frequency of DIE and posterior adenomyosis was higher in IBD than in Controls. A diagnosis of endometriosis, often mimicking IBD activity, should be considered in subgroups of female patients with IBD.